PEMBERDAYAAN REMAJA GUNA MENUMBUHKAN SEMANGAT KEAGAMAAN MELALUI SENI SHOLAWAT AL BANJARI - Ahmad Aly Syukron Aziz Al Mubarok; Abdul Hamid; Merry Liana; Mar'atus Saadah (Universitas Negeri Surabaya, 2023)
Empowerment is a development process where the community takes the initiative to start a process of social activities to improve their own situation and condition. There is a decrease in religious fervor in adolescents. The triggers are the low enthusiasm of adolescents to participate in religious activities and the lack of motivation from their parents, only about 25 teenagers become members with active membership status in a religious activity. The low understanding of adolescents about the importance of religious activities is a basic factor in the emergence of problems. Furthermore, the apathy of society towards adolescent problems is also a problem factor. To unravel these problems, it is necessary to empower youth in a structured manner. So we participated in carrying out several activities to empower youth through personal and community approaches, meet and great as well as training activities for the art skills of the al banjari sholawat. As a result, the youth of Kintelan village are more enthusiastic in carrying out religious activities, especially the al-banjari prayer.